2013
DOI: 10.1021/la3050863
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Supercritical Carbon Dioxide/Water/Quartz Systems: Simultaneous Measurement of Contact Angle and Interfacial Tension at Reservoir Conditions

Abstract: Injection of carbon dioxide in deep saline aquifers is considered as a method of carbon sequestration. The efficiency of this process is dependent on the fluid-fluid and rock-fluid interactions inside the porous media. For instance, the final storage capacity and total amount of capillary-trapped CO2 inside an aquifer are affected by the interfacial tension between the fluids and the contact angle between the fluids and the rock mineral surface. A thorough study of these parameters and their variations with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
186
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(214 citation statements)
references
References 29 publications
26
186
2
Order By: Relevance
“…Figure 2a. Results show that the advancing contact angle is considerably higher than the receding contact angle in the same pore throat, consistent with previous studies [18,22,[43][44][45]. The difference between ACA and RCA is attributed to the blemishes on non-ideal surfaces which results in pinning the interfaces to the solid surface [46].…”
Section: Contact Angle Measurementsupporting
confidence: 89%
See 3 more Smart Citations
“…Figure 2a. Results show that the advancing contact angle is considerably higher than the receding contact angle in the same pore throat, consistent with previous studies [18,22,[43][44][45]. The difference between ACA and RCA is attributed to the blemishes on non-ideal surfaces which results in pinning the interfaces to the solid surface [46].…”
Section: Contact Angle Measurementsupporting
confidence: 89%
“…Average contact angles on flat surface inside micromodel at pressure of one and eight megapascals are 62° ± 7° and 49° ± 21°, respectively, in agreement with Kim et al [58] observations showing a wide range of contact angles from 40° to 80° inside a uniform micromodel. Contact angles on a flat surface in this study are higher than those shown in previous sessile drop or captive bubble tests with large droplet of water or bubble of CO2 (i.e., 8° to 45° on silica or glass surface) [18,22,43,[50][51][52]. This could be due to the micro-scaled CO2 bubble size on a flat surface inside the micromodel of [18,22,43,[50][51][52].…”
Section: Comparing Contact Angle Of Bubbles On Flat Surface With Contcontrasting
confidence: 76%
See 2 more Smart Citations
“…A plethora of experimental and computational works is available on wetting behavior of reservoir fluids over mineral surfaces, such as quartz (Hou et al 2015;Saraji et al 2013;Wu et al 2013;Xuefen et al 2009), calcite (Benlia et al 2012Cebecia and Sönmezb 2004;Guiwu et al 2009;Khusainova et al 2015;Sakuma et al 2014; Electronic supplementary material The online version of this article (doi:10.1007/s13204-017-0563-1) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%